2014
DOI: 10.1016/j.vaccine.2014.08.069
|View full text |Cite
|
Sign up to set email alerts
|

Anti-pertussis antibody kinetics following DTaP-IPV booster vaccination in Norwegian children 7–8 years of age

Abstract: At the age of 7-8 years a booster of diphtheria, tetanus, acellular pertussis and polio vaccine is recommended for children in Norway. In this cross-sectional study we have analysed the antibody levels against pertussis vaccine antigens in sera from 498 children aged 6-12 years. The purposes of this study were to investigate the duration of the booster response against the pertussis vaccine antigens pertussis toxin (PT) and filamentous haemagglutinin (FHA); to determine the presence of high levels of pertussis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…This is consistent with the results of other studies where risk is seen to increase three years after the last acellular dose [5]. These findings should be incorporated into vaccination strategies decisions and they should promote research on new anti-pertussis vaccine components with greater effectiveness and longer protection.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with the results of other studies where risk is seen to increase three years after the last acellular dose [5]. These findings should be incorporated into vaccination strategies decisions and they should promote research on new anti-pertussis vaccine components with greater effectiveness and longer protection.…”
Section: Discussionsupporting
confidence: 89%
“…In recent years, an increase in the number of cases has been noticed in different European countries, including Spain, in spite of good vaccination coverage [3,4]. Studies have also indicated a decline in antigenic response to acellular vaccine already few years after vaccination booster and this could result in the near future in vulnerable age cohorts vaccinated exclusively with it [5,6]. This highlights that even a full course of acellular vaccine in line with the present vaccination schedules and good coverage may not confer sufficient protection to adolescents, and that there continues to be a risk of epidemic waves each three to four years [7,8].…”
Section: Epidemiological Contextmentioning
confidence: 99%
“…Both aP and wP induce an increase in antibody titers against all aP components [1114]. Adults originally primed with wP remain seropositive for multiple pertussis antigens up to 36 months following vaccination, with antibody titers at greater levels than at pre-vaccination [15].…”
Section: Introductionmentioning
confidence: 99%
“…Zepp et al (17) reported that a preschool booster reduced the total number of patients with pertussis in all generations, not only in the target group of school-aged children, because of indirect effects. In Norway, anti-PT antibodies were investigated at 6-12 years of age, and the results indicated that the level of immunity against pertussis was low at 5 years after the primary vaccination and that the DTaPbooster administered at 7-8 years generated a moderate anti-pertussis immune response that waned to near prebooster levels in a few years (18). Although a pre-school dose is administered at 4 years of age in the U.S., the highest incidence was in children aged 7-14 years, peaking at 10 years of age (9).…”
Section: Discussionmentioning
confidence: 99%